ASSERTIVES UTTERANCES IN SHORT INTERVIEW OF TOO COOL FOR MIDDLE SCHOOL’S YOUTUBE CHANNEL - Isniyati Isniyati (Universitas PGRI Semarang, 2021)
This study discusses the use of assertive acts uttered by the students in Short Interview of Too Cool for Mile School’s YouTube Channel. It explores how the acts of assertives are communicated by students during the interview. The subject of this study was students of Too Cool for Middle School’s YouTube Channel. The objective study are: 1) to find the types of assertive acts uttered by the students, 2) the meaning of use the assertives acts, and 3) the reason of the use of the assertives acts. This study uses descriptive qualitative. The data obtained from YouTube interview by a teacher on Too Cool for Mile School’s YouTube Channel. The students were given five questions in the about study at home to find the type of assertive acts and the meaning of the use of assertives acts. The data were analyzed using data analysis from short interview transcript to find out the result. The result of the study showed that: This kind of assertive speech act presented utterances about The results of this study show that there are eight types of assertives acts uttered by the students in the short interview namely asserting (18), informing (8), reporting (4), stating (3), arguing (2), claiming (2), assuring (1), denying (1).Second, the speakers' reasons in uttering assertive utterances. The reason of the students in producing assertive act is because the students have their own thoughts which are conveyed through assertive utterances.